2012
DOI: 10.4103/0972-124x.106932
|View full text |Cite
|
Sign up to set email alerts
|

Narrow diameter implant in posterior region

Abstract: Dental implants placement can sometimes be limited due to physical conditions, wherein the horizontal space is limited by adjacent teeth and roots or situations in which there is narrow alveolar ridge, By using a narrow diameter implant (NDI), the need for bone augmentation can be avoided. In situations where there is limited horizontal space, a NDI may be the only option to replace a missing tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore, careful recommendation and technique must be used. Therefore, success rate is high, as shown in several studies [12][13][14] . The use of 3.3 mm implants has also been highly satisfactory in relation to prosthetic units, with no clinical difference when compared to 4.1 mm diameter prosthetic implants in the posterior region of the mandible [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, careful recommendation and technique must be used. Therefore, success rate is high, as shown in several studies [12][13][14] . The use of 3.3 mm implants has also been highly satisfactory in relation to prosthetic units, with no clinical difference when compared to 4.1 mm diameter prosthetic implants in the posterior region of the mandible [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, several studies focused on testing the increase of the diameter and/or length of the implant or alterations in the macrogeometry thereof 10,11 . Previous studies have shown that the diameter of an implant has significant effects on the generation of tension/deformation of the peri-implant osseous tissue 12,13 . Several authors have suggested that an increase in the diameter favors the biomechanical issue for peri-implant osseous maintenance [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Implants known as “narrow”, according to the literature, have the following diameters [mm]: 1.8, 2, 2.2, 2.4, 2.5, 3.0, 3.3, 3.5, and 3.75 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Marc et al [ 38 ] suggested three categories of division of narrow implants:…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the diversity related to NDIs are still insufficient. The stability of posterior NDIs continues to be discussed [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%